PRELIMINARY PHYTOCHEMISTRY AND ANTIDIABETIC ACTIVITY OF PORTULACA GRANDIFLORA HOOK PLANT EXTRACT ON STREPTOZOTOCIN-INDUCED DIABETES IN RATS - DEVI M; KOMAL S; LOGESHWARI B (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was aimed to evaluate the antidiabetic activity of ethanolic extract of the whole aerial plant of Portulaca grandiflora Hook on streptozotocin (STZ)-induced diabetic rats. Methods: Experimental diabetes was induced by a single dose of intraperitoneal injection of STZ (150 mg/kg). Adult male Wister albino rats were divided into five groups; normal control, diabetic control, diabetic glibenclamide (5 mg/kg), diabetic P. grandiflora H. extract (200 mg/kg), and diabetic P. grandiflora H. extract (400 mg/kg) for 21 days and analyzed for body weight (BW) and blood glucose. Results: The STZ-treated diabetic control rats showed a significant increase in blood glucose with a concomitant decrease in BW. Oral administration of P. grandiflora H. extract (200 and 400 mg/kg) and glibenclamide (5 mg/kg) for 21 days showed a significant reduction in blood glucose levels and elevation in the bodyweight studies as compared to control and glibenclamide-treated rats. Conclusion: The results of the present study showed that a potent antidiabetic activity was present in the aerial part of plant P. grandiflora H. extract.